Madea's witness protection - Perry, Tyler; Hall, Paul; Areu, Ozzie; Levy, Eugene, 1946-; Richards, Denise, 1971-; Arnold, Tom, 1959-; Roberts, Doris, 1925-2016; Lil' Romeo, 1989-; Amos, John, 1939-; Gibbs, Marla, 1931-; Campbell, Danielle; Leos, Devan; et al. (Santa Monica, California Lionsgate, 2012)
A Wall Street banker has been involved with the mob in a Ponzi scheme, forcing him to enter witness protection with his family in Madea's house down South.
Originally released as a motion picture in 2012.
Special features: Tyler Perry- multi hats & costumes; Thank yur, Hellur- impersonating Madea; The Needlemans; Madea's fun house; Madea's comedy icons.
Director of photography, Alexander Gruszynski ; editor, Maysie Hoy ; music, Aaron Zigman.
Tyler Perry, Eugene Levy, Denise Richards, Doris Roberts, Romeo Miller, Tom Arnold, John Amos, Marla Gibbs, Danielle Campbell, Devan Leos.
MPAA rating: PG-13; for some crude sexual remarks and brief drug references.
DVD, region 1; widescreen (16x9, 1.78:1) presentation; Dolby Digital 5.1.
Keywords: Investment bankers -- Drama; Ponzi schemes -- Drama; DVD-Video discs; Comedy films; Films for the hearing impaired; Drama; Feature films; Fiction films; Video recordings for the hearing impaired